Defect Evolution in Cosmology and Condensed Matter Quantitative Analysis with the Velocity-Dependent One-Scale Model - Martins, C.J.A.P (SpringerBriefs in Physics, 2016)
This book sheds new light on topological defects in widely differing systems, using the Velocity-Dependent One-Scale Model to better understand their evolution. Topological defects - cosmic strings, monopoles, domain walls or others - necessarily form at cosmological (and condensed matter) phase transitions. If they are stable and long-lived they will be fossil relics of higher-energy physics. Understanding their behaviour and consequences is a key part of any serious attempt to understand the universe, and this requires modelling their evolution. The velocity-dependent one-scale model is the only fully quantitative model of defect network evolution, and the canonical model in the field. This book provides a review of the model, explaining its physical content and describing its broad range of applicability.